La Fiebre Chikungunya - Jorge R. Rey; C. Roxanne Rutledge-Connelly; Christopher N. Mores; Chelsea T. Smartt; Walter J. Tabachnick (EDIS)
ENY-736S, a 4-page fact sheet by Jorge R. Rey, C. Roxanne Connelly, Christopher N. Mores, Chelsea T. Smartt, and Walter J. Tabachnick, is the Spanish language version of ENY-736, "Chikungunya" It describes this mosquito-borne virus, what it is, its symptoms, how its transmitted to humans, where it occurs, risk to Floridians, and how it can be prevented. Includes references. Published by the UF Department of Entomology and Nematology, July 2007.